AN ANALYSIS OF HIGHER ORDER THINKING SKILL (HOTS) IN MERDEKA CURRICULUM ENGLISH TEXTBOOK â€œPATHWAY TO ENGLISHâ€ PUBLISHED BY ERLANGGA FOR GRADE X OF SENIOR HIGH SCHOOL - Arisman, Arisman; Maisarah, Ira; Yunita, Wisma; Sujarwati, Iis; Sofyan, Dedi (Universitas Khairun, 2024)
Higher order thinking skills (HOTS) refer to the more advanced mental processes outlined in Anderson and Krathwohl's updated version of Bloom's taxonomy (2021), comprising analysis, evaluation, and creation.